KINERJA PELAYANAN PUBLIK DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KEPULAUAN MERANTI - Akrolina, Wisa; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Civil service and civil registration is one of the government agencies engaged in the field of community service and implementation. Public services are the renponsibility of the government by central and local. The current conditions obtained in the impelementation of public services is still faced with the system of government that has not been effective and afficien and the quality of human resources apparatus is not adequate.The purpose of this study was to analyze the performance of public service in the civil service and civil registry of Meranti island districts and to analyze the factors that hinder the performance of public service in the civil service and civil registry of Meranti island districts. The method used in this study is a qualitative research method. Sources of data were drawn from severah people related to the research, among others, the secretary of processing section of population and community data. Data colletion techniques using observation and documentation interview techniques while the data analysis techniques used in this study is descriptive qualitative analysis.Based on the results of the study note that the performance in the civil service and civil registration districts meranti archipelago is still not optimal and influenced by several factors that have not had the soup and goal setting.Keywords : performance, public service, Human Resources Management